EVOLUÇÃO DOS MEDICAMENTOS GENÉRICOS NO BRASIL (REMUNOM, 2023)
Generic medicines, which are essential components for health, are currently receiving attention due to the way in which they are used and reflect their therapeutic effects. They are available at affordable prices thanks to the federal government's National Drug Policy (PNM), which has been in place since 1999 to allow patients to choose high-quality drugs. When the name of the active principle is mentioned in the prescription, the reference medicine may be substituted by the generic. The objective of this work was to understand the evolution of generic drugs in Brazil, providing information on the importance and safety of these drugs for the population and demystifying the idea that these drugs are cheaper due to lack of quality, efficacy or ambiguous safety. This study is characterized by being a bibliographical survey, composed of several publications in magazines, books, monographs, doctoral theses and dissertations. The study made it possible to verify the association of generic medicines with reference medicines, research that allowed us to understand the importance of people understanding the benefits of buying generics through promotional campaigns and realizing that they work in the same way as the brand medicine. brand. reference, since both have the same active ingredient. Thus, this study allowed us to analyze that generic drugs are as relevant as the reference drug, in addition to offering benefits to both the market and the population since their implementation in the country. Therefore, it was important to consider that Brazilians should understand the benefits of buying these drugs and be aware that generics follow the same principle as brand drugs. Given this, it is believed that more public information campaigns on generic drugs are needed for the population. Keywords: Generic Drugs; Health; Prices; Information.